A novel mRNA vaccine, SYS6006, against SARS-CoV-2 - Xu, Ke; Lei, Wenwen; Kang, Bin; Yang, Hanyu; Wang, Yajuan; Lu, Yanli; Lv, Lu; Sun, Yufei; Zhang, Jing; Wang, Xiaolin; Yang, Mengjie; Dan, Mo; et al. (Frontiers in Immunology, 2023)
The development of vaccines that can efficiently prevent the infection of SARS-CoV-2 is necessary to fight the COVID-19 epidemic. mRNA vaccine has been proven to induce strong humoral and cellular immunity against SARS-CoV-2. Here, we studied the immunogenicity and protection efficacy of a novel mRNA vaccine SYS6006. High expression of mRNA molecules in 293T cells was detected. The initial and boost immunization with a 21-day interval was determined as an optimal strategy for SYS6006. Two rounds of immunization with SYS6006 were able to induce the neutralizing antibodies against the SARS-CoV-2 wild-type (WT) strain, and Delta and Omicron BA.2 variants in mice or non-human primates (NHPs). A3rd round of vaccination could further enhance the titers of neutralization against Delta and Omicron variants. In vitro ELISpot assay showed that SYS6006 could induce memory B cell and T cell immunities specifically against SARS-CoV-2 in mice. FACS analysis indicated that SYS6006 successfully induced SARS-CoV-2-specific activation of T follicular helper cell (Tfh) and Th1 cell, and did not induce CD4+Th2 response in NHPs. SYS6006 vaccine could significantly reduce the viral RNA loads and prevent lung lesions in Delta variant infected hACE2 transgenic mice. Therefore, SYS6006 could provide significant immune protection against SARS-CoV-2.